2007
DOI: 10.1097/qai.0b013e318042d5e3
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic Effects of Maternal Antiretroviral Therapy and Transmission Prophylaxis in HIV-1-Exposed Uninfected Newborn Infants

Abstract: Antiretroviral transmission prophylaxis is associated with significant anemia and neutropenia in HIV-uninfected infants during the first 3 months of life. Anemia was more profound in HAART-exposed infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
42
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 31 publications
6
42
0
1
Order By: Relevance
“…These observations are consistent with short-term hematological disturbances seen in clinics (12,25). However, in this pilot study, no correlation was found between intracellular NRTI-MP/TP concentrations and short-term toxicity data at birth and at 1 month, 3 months, and 6 months of age.…”
Section: Discussionsupporting
confidence: 79%
“…These observations are consistent with short-term hematological disturbances seen in clinics (12,25). However, in this pilot study, no correlation was found between intracellular NRTI-MP/TP concentrations and short-term toxicity data at birth and at 1 month, 3 months, and 6 months of age.…”
Section: Discussionsupporting
confidence: 79%
“…A previous study showed that newborns are likely to be overexposed to AZT/AZT-MP/AZT-TP and 3TC-TP during the first 2 weeks of life (10). These observations are consistent with short-term hematological disturbances seen in clinics (7,11). However, no correlation was found between intracellular nucleoside reverse transcriptase inhibitor monophosphate (NRTI-MP)/TP concentrations and short-term toxicity data at birth and at 1, 3, and 6 months of age.…”
Section: Discussionsupporting
confidence: 77%
“…Newborns are likely to be overexposed to intracellular phosphorylated nucleoside reverse transcriptase inhibitors (NRTIs), as was shown for lamivudine triphosphate (3TC-TP) and zidovudine triphosphate (AZT-TP) during the first 2 weeks of life (10). Indeed, high levels of AZT/AZT monophosphate (AZ-MP)/AZT-TP, and 3TC-TP were consistent with short-term hematological disturbance observed in clinics (7,11). If, as suggested by the literature (10), this overexposure was related to a more efficient phosphorylation due to a higher activation in the peripheral blood mononuclear cells (PBMCs) of the neonates than in adults, it could be the same for TFV-DP and could cause…”
mentioning
confidence: 89%
“…Also, the antiretroviral (ARV) prophylaxis of vertical transmission can act on the placental environment, causing changes in cytokine expression (9). The newborns present abnormalities in mitochondrial function (2), in hematological features (5,10,17), and in the maturation of T and B lymphocytes (3,4,8,11,12,20,24,25).…”
mentioning
confidence: 99%